Strategi Dan Efektifitas Komunikasi Organisasi Dalam Mengatasi Konflik Kerja Di Lingkungan Humas Pemko Medan - Andika Suhartono; Wardayani Wardayani (Universitas Dian Nuswantoro, 2022)
This study aims to find out how the strategy and effectiveness of organizational communication in overcoming work conflicts in the Pemko Medan Public Relations environment. Managing individual behavior towards the internal organization really needs to be done so that the communication that is established becomes effective. Effective communication will determine the quality of results and the process of achieving organizational goals. But on the contrary, if individuals cannot minimize the conflicts that occur within an organization, it will be able to have adverse effects such as feelings of discomfort and decreased work motivation of every member of the organization. Individuals who understand organizational management have a role in reducing and resolving conflicts that occur within the organization. And by maintaining effective communication, it will be able to reduce conflicts that occur within the organization.